A study of iron deficiency among blood donors in HUSM - Jamil, Norashikin (Pusat Pengajian Sains Kesihatan, Universiti Sains Malaysia, 2005)
Regular blood donation can result in iron deficiency among blood donors. This is due to regular iron loss from each donated whole blood wtit. If not treated or controlled, the condition might lead to the development of iron deficiency anemia. The objective of this study was to determine the prevalence of iron deficiency among blood donors of Hospital Universiti Sains Malaysia (HUSM). This was a cross - sectional study, conducted at Transfusion Medicine Unit of HUSM and also other provinces which were randomly selected namely Tanah Merah, Tumpat, Bachok and Kota Barn, Kelantan. A total of 211 eligible male blood donors had taken part and they were categorized into three groups. The first group was made of the first time donors (43.6%) and they were the control group of this study. The second group consisted of donors who had donated from two to four times only (19 .4%) and the third group comprised of the regular donors who had donated equal to or more than five times previously (37 .0%). All donors had passed the haemoglobin concentration test by HemoCue prior to donation. 5 ml of blood was drawn for the detetmination of body iron stores evaluated by serum ferritin measurement. The cut - off point of serum ferritin was based of WHO guideline ( <15 J.Lg/1). Among the donors, 4% were iron- deficient. From the prevalence, 44% were the first time donors and 56% were regular donors. Serum ferritin level were found to be significantly lower among the regular donor (62.0 ± 39.78 Jlg/1) as compared to the first time donors (90.17 ± 66.63 Jlg/1) and the second group donors (114.12 ± 66.97 Jlg/1). There was a significant (fair) correlation between frequency of donation and serum ferritin level (P <0.001). However, there was no correlation between haemoglobin concentration and serum ferritin level (P = 0.76). It is concluded that the used of haemoglobin measurement as a single parameter to screen blood donors should be reviewed. It is also suggested that besides haemoglobin estimation, serum ferritin assessment should also be included in the screening protocol for blood donors, especially for the regular donors who had donated for more than five time per two years.